A RE-AIM Evaluation of a Visualization-Based Electronic Patient-Reported Outcome System - Turchioe, Meghan Reading; Mangal, Sabrina; Goyal, Parag; Axsom, Kelly; Myers, Annie; Liu, Lisa G.; Lee, Jessie; Campion, Thomas R., Jr.; Creber, Ruth Masterson (Applied Clinical Informatics, 2023)
Objectives Health care systems are primarily collecting patient-reported outcomes (PROs) for research and clinical care using proprietary, institution- and disease-specific tools for remote assessment. The purpose of this study was to conduct a Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) evaluation of a scalable electronic PRO (ePRO) reporting and visualization system in a single-arm study.Methods The “mi.symptoms” ePRO system was designed using gerontechnological design principles to ensure high usability among older adults. The system enables longitudinal reporting of disease-agnostic ePROs and includes patient-facing PRO visualizations. We conducted an evaluation of the implementation of the system guided by the RE-AIM framework. Quantitative data were analyzed using basic descriptive statistics, and qualitative data were analyzed using directed content analysis.Results Reach—the total reach of the study was 70 participants (median age: 69, 31% female, 17% Black or African American, 27% reported not having enough financial resources). Effectiveness—half (51%) of participants completed the 2-week follow-up survey and 36% completed all follow-up surveys. Adoption—the desire for increased self-knowledge, the value of tracking symptoms, and altruism motivated participants to adopt the tool. Implementation—the predisposing factor was access to, and comfort with, computers. Three enabling factors were incorporation into routines, multimodal nudges, and ease of use. Maintenance—reinforcing factors were perceived usefulness of viewing symptom reports with the tool and understanding the value of sustained symptom tracking in general.Conclusion Challenges in ePRO reporting, particularly sustained patient engagement, remain. Nonetheless, freely available, scalable, disease-agnostic systems may pave the road toward inclusion of a more diverse range of health systems and patients in ePRO collection and use.
Keywords: patient-reported outcomes; patient engagement; data visualizations; remote assessment